Improving critical thinking and creative thinking skills through POPBL learning in high school student - Rima Suwistika; I. Ibrohim; Hendra Susanto (University of Muhammadiyah Malang, 2024)
Education in the 21st century has experienced many advances that are adjusted to the demands of the times. Thinking skills are in high demand in the 21st century, especially critical thinking and creative thinking skills for students. This study aims to determine the effectiveness of POPBL model learning in improving critical and creative thinking skills of high school students. This type of quasi-experimental research was carried out with a nonequivalent control group design. The population of this study was students of class XI MIPA SMAN 1 Cluring with two classes XI MIPA 1 and XI MIPA 2 as samples. The data collection method is in the form of tests of critical thinking skills and creative thinking. The data analysis used is an analysis of covariance test. The results showed that POPBL was effective in improving the critical thinking and creative thinking skills of SMAN 1 Cluring students. The implementation of POPBL learning shows interaction between students at work as well.